DISTRIBUTION OF THE RETAIL PRICES OF DAIRY PRODUCTS AMONG SUPPLY CHAIN PARTICIPANTS IN LITHUANIA - Deiva MIKELIONYTĖ; Ovidija EIČAITĖ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study aims at evaluating the developments in the distribution of the retail prices of dairy products among supply chain participants in Lithuania over the period of 2008 to 2017 and at revealing the main factors that determine this distribution. In order to achieve this aim, the structure of the Lithuanian dairy supply chain has been examined and the shares of milk producers, dairy processors, retailers and state (VAT) in the retail prices of dairy products (drinking milk and Tilsit cheese) have been calculated. The structure of the Lithuanian dairy supply chain indicates that milk producers, a large majority of which are small-scale dairy farmers, are fragmented and less organized, while the dairy processing industry and retail trade can be considered as heavily concentrated. Over the past ten years, the shares of retailers in the retail prices of dairy products have shown an increase, while the shares of milk producers in these prices have decreased. Horizontal concentration and vertical integration are the main instruments that could help to increase the market power of milk producers. Furthermore, milk producers should be opened to entering direct sales marketing, or short food supply chains.